Nuclear reaction and structure effects near and beyond the β-stability line - Kumar, Mahesh (My University, 2016)
In the present thesis an attempt has been made to investigate the structure and reaction dynamics of some light mass nuclei from the valley of stability to drip line. The structure behavior of these nuclei is studied by using well known microscopic Relativistic and Nonrelativistic mean filed formalism. The densities of these formalisms are primary major input for the reaction dynamics in Glauber model. The detail of our work is given in the following chapters. The thesis consists of seven chapters. A brief outline of the chapters is as follow: Chapter 1 Chapter I of the thesis is introductory in nature which includes a brief survey of the nuclear phenomenon which occurs in these days. A summary of recent methods and work of succeeding chapters is also given. Chapter 2 Chapter II consists the brief descriptions of the formalisms which include mean field formalisms. The non-Relativistic mean field and relativistic mean field formalisms are used to investigate the structural properties. The Glauber model is also described for the reaction dynamics in this chapter. Chapter 3 In this chapter, we have investigated the bulk properties of nuclear systems. The Ground state properties like binding energy, root mean square charge radius, quadrupole deformation and nucleonic density distributions etc. are described after obtained from the relativistic and nonrelativistic mean field formalisms. The estimated values of bulk properties are also compared with the available experimental data. Chapter 4 Chapter IV, we have studied the density distributions of some light mass nuclei in the frame-work of the non-relativistic Hartree-Fock and the relativistic mean field formalisms in light mass region. The structure and bubble effect for 22O, 23F, 34Si, 36S,36Ar and 46Ar nuclei is studied. Such effect is of huge relevance in the drip-line and the superheavy region. Chapter 5 In this chapter, we have discussed the reaction cross sections of light mass nuclei using Glauber model with densities from relativistic and non-relativistic mean field formalism. A list of various inputs of the Glauber model is also given in this chapter. The mean field densities of projectile and target nuclei are converted in the form of Gaussian coefficients and listed in the chapter in terms of 2 Gaussian and 4 Gaussian coefficients. The sensitivity of converted densities has been checked with the RMF and HF densities in terms of their density profiles. An effort is made to address the structure effects in the context of dynamical evolution of the nuclear systems. A comparative study of the reaction cross sections using densities from RMF and non-RMF formalism Chapter 6 Chapter VI contains the discussion of structural properties and reaction dynamics of halo nuclear systems. The results are also compared with the experimental data which are available. We also try to extend our formalisms for the investigation of recently observed 31Ne and 37Mg halo nuclear systems. Chapter 7 Conclusion based on the present study is finally drawn in the concluding chapter VII. The significance of the present work and scope of future research work is also discussed in this concluding chapter.
PHD, SPMS
Keywords: Nuclear Reaction; Nuclear structure; SPMS